Pengaruh Brand Ambassador, Brand Image, Word of Mouth dan Kualitas Produk terhadap Keputusan Pembelian Produk Mlaku Coffee - Roni Caniago; Arini Hidayah; Tri Septin Muji; Alfato Yusnar Kharismasyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to analyze the effect of Brand Ambassador, Brand Image, Word of Mouth and Product Quality on Purchasing Decisions for Mlaku Coffee Products in Purwokerto.The sampling method in this study used non-probability sampling technique, namely purposive sampling. Based on the criteria, 100 respondents were obtained as a sample. The method used in this research is to use quantitative research with data collection using a questionnaire in the form of a 1-5 Likert scale to respondents who have purchased Mlaku Coffee products who live in Purwokerto. The data analyzed is primary data collected through questionnaires and processed using the SPSS version 26 program. The data analysis used in this study is multiple linear regression analysis test. Based on the results of the analysis, it shows that Brand Ambassador has a positive and significant effect on purchasing decisions. Brand Image has no positive effect on purchasing decisions. Word of Mouth has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions.